2021
DOI: 10.1038/s41467-021-21255-8
|View full text |Cite
|
Sign up to set email alerts
|

The acquisition of molecular drivers in pediatric therapy-related myeloid neoplasms

Abstract: Pediatric therapy-related myeloid neoplasms (tMN) occur in children after exposure to cytotoxic therapy and have a dismal prognosis. The somatic and germline genomic alterations that drive these myeloid neoplasms in children and how they arise have yet to be comprehensively described. We use whole exome, whole genome, and/or RNA sequencing to characterize the genomic profile of 84 pediatric tMN cases (tMDS: n = 28, tAML: n = 56). Our data show that Ras/MAPK pathway mutations, alterations in RUNX1 or TP53, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 87 publications
4
39
1
Order By: Relevance
“…This novel dysregulation of the SWI/SNF chromatin-remodeling complex appears a key driver in tMN harboring evidence of chemotherapy-induced mutagenesis. Consistent with previous evidence the MECOM locus was also frequently involved by tMN structural variation; with a preponderance for tMN containing a chemotherapy-associated signature (3 of 4 cases, Fig 2c, Extended Data Fig 10 ) 36 .…”
Section: The Genomic Driver Landscape Of Therapy-related Myeloid Neop...supporting
confidence: 90%
“…This novel dysregulation of the SWI/SNF chromatin-remodeling complex appears a key driver in tMN harboring evidence of chemotherapy-induced mutagenesis. Consistent with previous evidence the MECOM locus was also frequently involved by tMN structural variation; with a preponderance for tMN containing a chemotherapy-associated signature (3 of 4 cases, Fig 2c, Extended Data Fig 10 ) 36 .…”
Section: The Genomic Driver Landscape Of Therapy-related Myeloid Neop...supporting
confidence: 90%
“…Whole-genome sequencing data analysis. WGS analysis (n=91) were performed using standard methods as described (15,24). Briefly, DNA reads were mapped using BWA (WGS: v0.7.15-r1140, RRID:SCR_010910) to the GRCh37-lite/hg19 human genome assembly.…”
Section: Subjectmentioning
confidence: 99%
“…26,28,29 However, in a recent analysis of 84 pediatric patients with tMN, which included many patients also included in this study, investigators found that contrary to adults with tMN , in pediatric patients with tMN there was no evidence of pre-existing minor clones with germline mutations. 30 KMT2Ar and Ras/MAPK pathway mutations were the most common driver alterations in pediatric patients with tMN, and while TP53 mutations were identified, these were not present in the germline like in the adult tMN patients. 30 However, recent studies have shown that some pediatric tMN patients may have a genetic mutational signature similar to relapsed mismatch repair-deficient ALL, 30,31 which could imply a poor tolerance to genotoxic conditioning.…”
Section: Discussionmentioning
confidence: 95%
“…30 KMT2Ar and Ras/MAPK pathway mutations were the most common driver alterations in pediatric patients with tMN, and while TP53 mutations were identified, these were not present in the germline like in the adult tMN patients. 30 However, recent studies have shown that some pediatric tMN patients may have a genetic mutational signature similar to relapsed mismatch repair-deficient ALL, 30,31 which could imply a poor tolerance to genotoxic conditioning. Short telomere length, due to inherited genetic syndromes or acquired exposures, may also lead to impaired cellular recovery after myeloablative conditioning and therefore increased toxicity from transplantation.…”
Section: Discussionmentioning
confidence: 95%